2018
DOI: 10.1001/jamafacial.2017.0644
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of W-Plasty and Straight-Line Trichophytic Closure on Aesthetic Outcomes of Occipital Hairline Scars in Rhytidectomy

Abstract: IMPORTANCE Incision placement and design in rhytidectomy is critical for patient satisfaction.OBJECTIVE To evaluate the aesthetic outcome of W-plasty vs traditional straight-line (SL) trichophytic closure techniques on posterior occipital hairline scars in rhytidectomy. DESIGN, SETTING, AND PARTICIPANTSA retrospective cohort study was conducted at the Buckingham Center for Facial Plastic Surgery. Clinical history and operative reports were reviewed for 46 patients who underwent rhytidectomy (23 using W-plasty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…Some studies have found that the W‐plasty technique is significantly better than SL resection, and other studies have shown that there is no statistical difference between the two methods of skin closure. 4 , 8 , 9 In our previous study, we confirmed that the technique of CTR with a tension offloading device could effectively decrease the tension across the surgical incision and significantly reduce the keloid recurrence rate and achieve therapeutic efficacy. 13 In the research presented here, we first introduce the concept of CTR into traditional W‐plasty, aiming to overcome the drawbacks of using W‐plasty technology alone.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Some studies have found that the W‐plasty technique is significantly better than SL resection, and other studies have shown that there is no statistical difference between the two methods of skin closure. 4 , 8 , 9 In our previous study, we confirmed that the technique of CTR with a tension offloading device could effectively decrease the tension across the surgical incision and significantly reduce the keloid recurrence rate and achieve therapeutic efficacy. 13 In the research presented here, we first introduce the concept of CTR into traditional W‐plasty, aiming to overcome the drawbacks of using W‐plasty technology alone.…”
Section: Discussionsupporting
confidence: 58%
“…The literature reports and the results of this study show that although the SL incision combined with CTR technique can make the incision scar very thin, it is still unsatisfactory. 4 , 7 , 18 In contrast, W‐plasty had a camouflaging effect in relation to RSTLs. After surgery, a ‘broken‐line’ or accordion appearance allows the scar to break down into smaller triangles with at least one side parallel to a poorly defined RSTL, which causes light scattering and leads to a scar that is less noticeable to observers.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…For unfavorable scar healing, treatment options such as dermabrasion, laser, interlesional injections, and surgical scar revisions can be performed at a later time. While this study does not analyze the post-auricular incision, there are recommended techniques on incision placement to maximize aesthetic outcomes and minimize wound tension, such as but not limited to using W-plasty along the occipital hairline 6 and avoiding incision placement within the post-auricular sulcus. 7…”
Section: Discussionmentioning
confidence: 99%